Fetal alcohol syndrome - O'Leary, Colleen; Bower, C. (Therapeutic Guidelines Limited, 2012)
Fetal alcohol spectrum disorder (FASD) is the umbrella term for a range of clinically significant fetal effects of alcohol. It is not a clinical diagnosis. Fetal alcohol syndrome (FAS) is the most easliy recognised FASD, due to its characteristic facial features. Other FASD diagnoses include:-partial fetal alcohol syndrome-alcohol-related neurodevelopmental disorders-alcohol-related birth defects.Other terms that may be used include fetal alcohol effects (FAE) and static encephalopathy (alcohol exposed).The prevalence of FAS at birth varies between countries, and between ethnic groups within countries. Data from Western Australia in 2005 showed an overall prevalence of 0.5 in 1000 (Note 80), but it was 100 times higher in Aboriginal children (Note 81). Overseae estimates and recent research indicate that these figures are probably an underestimate.